1990
DOI: 10.1051/apido:19900402
|View full text |Cite
|
Sign up to set email alerts
|

Numbers of spermatozoa in queens and drones indicate multiple mating of queens in Apis andreniformis and Apis dorsata

Abstract: Summary — Drones of Apis dorsata had an average of 2.46•10 6 spermatozoa in their vesiculae seminales. Two queens had 3.67•10 6 spermatozoa in their spermathecae. In A adreniformis, drones had an average of 0.13•10 6 and the spermathecae of 2 queens contained 0.98 and 1.09•10 6 spermatozoa. In both A dorsata and A andreniformis the spermathecae of queens contained more spermatozoa than the vesiculae seminales of a single drone of either species. Therefore, we conclude that multiple ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 8 publications
(12 reference statements)
0
14
0
1
Order By: Relevance
“…The highest number counted in the present study was 2.04 × 10 6 and in the study of Tan et al (1996) it was 2.65 × 10 6 . The study of Koeniger et al (1990) aimed to demonstrate that A. dorsata queens mated more than once and was not intended to represent the average number of spermatozoa for drones in A dorsata species.…”
Section: Discussionmentioning
confidence: 99%
“…The highest number counted in the present study was 2.04 × 10 6 and in the study of Tan et al (1996) it was 2.65 × 10 6 . The study of Koeniger et al (1990) aimed to demonstrate that A. dorsata queens mated more than once and was not intended to represent the average number of spermatozoa for drones in A dorsata species.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of spermatozoa (million/mm 3 ) in the spermatheca is similar in all studied species: concentrations of fully mated, ovipositing queens normally range between 3 and 5 million/mm 3 [5]. In A. andreniformis up to 1.26 million spermatozoa were counted in the spermatheca with volumes of about 0.28 mm 3 , which corresponds to 4.63 million spermatozoa per 1 mm 3 [5]. There are no reported sperm numbers of queens that have successfully initiated oviposition after mating flights.…”
Section: Number Of Spermatozoa In the Spermathecamentioning
confidence: 85%
“…In 2 ovipositing queens, sperm numbers in the spermathecae were counted and compared with the sperm number from the vesiculae seminales of drones [5]. According to these sperm counts, it was suggested that queens mate a minimum of 8 times.…”
Section: Original Articlementioning
confidence: 99%
See 2 more Smart Citations